2007
DOI: 10.1071/fp07067
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition and D1 protein degradation in mesophyll and agranal bundle sheath thylakoids of maize

Abstract: Susceptibility of photosystem II complex (PSII) to photoinhibition and degradation of D1 protein has been described in the chloroplasts of C3 plants but so far, the PSII turnover has not been characterised in any C4 plant, which contains two types of chloroplasts differing biochemically and structurally. In maize (Zea mays L. Oleńka), chloroplasts located in mesophyll (M) develop grana, while bundle sheath (BS) chloroplasts are agranal. In this paper, we report the D1 protein phosphorylation, damage and proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…Interestingly, DDM caused more intensive detachment of CP43 compared with digitonin (data tot shown), in agreement with Heinemeyer et al (35). It cannot be excluded that a subpool of the PSII devoid of CP43 may be a product of the PSII repair cycle, since this pathway has been shown to exist in the BS agranal membranes (22). Additional experiments are required to test this possibility.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, DDM caused more intensive detachment of CP43 compared with digitonin (data tot shown), in agreement with Heinemeyer et al (35). It cannot be excluded that a subpool of the PSII devoid of CP43 may be a product of the PSII repair cycle, since this pathway has been shown to exist in the BS agranal membranes (22). Additional experiments are required to test this possibility.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, it was demonstrated that the level of PSII activity in BS chloroplasts, as well as the presence of the oxygen-evolving complex subunits, depends on the differences in the age of the source leaf tissue, contamination with MS chloroplasts during isolation procedures, and illumination conditions (14,20,21). The apparent existence of the D1 degradation/repair cycle in BS chloroplasts and the identification of proteolytic enzymes responsible for these processes in these organelles confirm that PSII indeed plays an important function in the BS agranal membranes (22). Indeed, the active dimeric PSII complexes present in the stroma lamellae of C 3 chloroplasts have been shown to undergo the repair cycle (23,24), whereby PSII with a damaged D1 reaction center subunit migrates from the grana to the stroma and subsequently undergoes disassembly, repair, and refolding (25).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The chlorophyll a/b ratio of maize and sorghum is significantly higher in agranal BS tissues compared with granacontaining M cells, as reported earlier (Ku et al, 1974;Pokorska and Romanowska, 2007). The higher chlorophyll a/b ratio, and the higher ratios of chlorophyll fluorescence under liquid nitrogen temperature at 730/685 nm for thylakoids of M than for BS thylakoids (5-to 6-fold), are indicative of a much higher abundance of LHCI-PSI complexes in BS thylakoids of Fluorescence spectra of chloroplasts of M and BS cells from maize and sorghum and of isolated grana core and stroma lamellae from Arabidopsis.…”
supporting
confidence: 71%
“…Evidently, this structural separation is not present in agranal BS cells of C 4 plants. Interestingly, the degradation of photodamaged PSII in maize is significantly faster in agranal BS chloroplasts than in M cells (Pokorska and Romanowska, 2007). This could be due to faster migration of damaged components of PSII in agranal membranes.…”
Section: Discussionmentioning
confidence: 90%